2022
DOI: 10.1186/s12917-022-03325-1
|View full text |Cite
|
Sign up to set email alerts
|

Success rate of artificial insemination, reproductive performance and economic impact of failure of first service insemination: a retrospective study

Abstract: Background A retrospective cohort study using a 10 year artificial insemination (AI) and cow reproductive performance data was conducted to study the success rate of AI; associations between effectiveness of AI and breed, AI season and, number of service per conception, and economic impact of failure of FSC in Dessie town, Dessie zuria and Kutaber districts. A total of 3480 dairy cows’ AI and reproductive performance records which were performed between 2003 and 2013 in the three selected distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The economic health of the farm is directly impacted by the cows' first-service conception rate. Although the percentage success of the first service ranged from 26.7 to 50.7% in prior research ( 6 , 7 ), conception during the first service after calving is crucial for cows to operate at their best reproductively. The expense of semen and the work required for heat checking and breeding for numerous AI are modest for this group ( 8 ).…”
Section: Introductionmentioning
confidence: 94%
“…The economic health of the farm is directly impacted by the cows' first-service conception rate. Although the percentage success of the first service ranged from 26.7 to 50.7% in prior research ( 6 , 7 ), conception during the first service after calving is crucial for cows to operate at their best reproductively. The expense of semen and the work required for heat checking and breeding for numerous AI are modest for this group ( 8 ).…”
Section: Introductionmentioning
confidence: 94%
“…Mekonnen et al (2010) on the other hand, discovered that the rst service NRR in the retrospective and eld follow-up studies was 86.6% and 48.2 %, respectively. Furthermore, a retrospective study by Tadesse et al(2022) revealed that the NRR at rst insemination was 86.55%. The effects of sire, calving season, and dam age on NRR at 60 and 90 days were signi cant (P < 0.05).…”
Section: Calving Interval (Ci) and Days Open (Do)mentioning
confidence: 99%
“…Bovine cloning by somatic cell nuclear transfer (SCNT) has the potential for application in the continuation of germplasm from animals with superior traits and has been widely employed to produce genome-edited animals for breed improvement. [1][2][3] Higher cloning efficiency (5%-10%) has been demonstrated in bovine as compared to other mammalian species 4,5 ; however, production rates from bovine SCNT remain dramatically lower than those from embryos generated in vivo (50%-80%), 6,7 limiting its practical application.…”
Section: Introductionmentioning
confidence: 99%